MEMPROGRAMKAN PENGENALAN BANK SYARIAH PADA DESA CIBITUNG WETAN, KECAMATAN PAMIJAHAN, KABUPATEN BOGOR - Trihantana, Rully; ME, Azizah Mursyidah; Khoiri, Abdul (Jurnal Pengabdian Kepada Masyarakat Perbankan Syariah: Program Studi Perbankan Syariah., 2023)
This community service aims to introduce Islamic banking in detail. The subject of this community service is the people of Cibitung Wetan Village, Pamijahan District, Bogor Regency, West Java Province. In community service activities are carried out based on counseling methods or interactive lectures. The result of this community service is that counseling and introductions about Islamic banking will be carried out in depth and detail by involving the Cibitung Wetan Village with the Center for Islamic Economics and Business Studies at Institut Agama Islam Sahid Bogor, then a process such as routine counseling on sharia banking will be carried out. With this community service, it can be concluded that this activity aims to introduce literacy about Islamic banking to all levels of society in Cibitung Wetan Village as well as by carrying out activity evaluations when introducing Islamic banks.